Ectopic Pregnancy in Tigray, Ethiopia: A Cross-Sectional Survey of Prevalence, Management Outcomes, and Associated Factors. (30th November 2021) - Berhe, Elsa Tesfa; Kiros, Kalayu; Hagos, Merhawit Gebremeskel; Gesesew, Hailay Abrha; Ward, Paul R.; Gebremeskel, Teferi Gebru
Abstract : Background . Ectopic pregnancy is a neglected and challenging gynecologic problem in developing countries including Ethiopia. Objective . The present study is aimed at assessing the prevalence of ectopic pregnancy, its management outcomes, and factors associated with management outcomes in Tigray, North Ethiopia. Methods . We employed a four-year retrospective cross-sectional study from September 2015 to August 2019. We extracted data about all pregnant mothers who were admitted and managed for EPs in Axum, Tigray. Ectopic pregnancy and its outcomes (favorable and unfavorable) were the dependent variables, and age, residence, ethnicity, religion, parity, history of abortion, history of EP, pelvic infections, history of surgical procedures, and use contraceptives were the independent variables. We employed descriptive statistics and bivariate and multivariate logistic regression analyses using SPSS. Ethical clearance was obtained from Axum University, Tigray, Ethiopia. Results . The overall prevalence of ectopic pregnancy was 0.52% of total deliveries, which equates to 1 : 193 deliveries. Surgery for ectopic pregnancy accounts for 7.6% of all gynecological surgeries. Most participants were in the age group 26–30 years and lived in rural areas. Among the different EP implantation sites, most cases (92.4%) occurred in the fallopian tube, followed by 5.1% in the ovary and 2.5% in abdominal EPs. Surgical management (laparotomy) was undertaken for all the 79 women diagnosed with EPs, including laparotomy (100%), salpingo-oophorectomy (17.7%), salpingectomy (73.9%), oophorectomy (3.4%), cornual resection (2.5%), and removal of concepts tissue 2.5. The record reports that intraoperative procedure was correctly managed for 47 (59.5%) women but the condition of EP procedure was ruptured for about two-thirds (63.3%) of the women. Thirty (38%) patients had developed some complications after surgery including anemia (hemoglobin < 10.5 ) ( n = 12 ), fever (n = 10 ), wound infection (n = 2 ), and pneumonia (n = 2 ). Women who were from urban (AOR = 11.2, 95% CI: 2.65-47.2) and who had normal hemoglobin at presentation (AOR = 9.94, 95% CI: 2.03-48.7) were associated with favorable maternal outcomes. Conclusions . More than one-third of women with ectopic pregnancies had an unfavorable maternal outcome, which was higher among rural residents and anemic mothers. Women living in rural areas and anemia during pregnancy should seek special attention in the management of EPs. We also recommend improving the data management of hospitals in Ethiopia.